Introduction to logic design - Marcovitz, Alan B. (McGraw-Hill Higher Education, 2005)
Introduction to Logic Design is intended for a first course in logic design, taken by computer science, computer engineering, and electrical engineering students (most commonly in the sophomore year). Its special strengths are a clear presentation of fundamentals with an exceptional collection of examples, solved problems, and exercises. The text integrates laboratory experiences, both hardware and computer simulation, while not making them mandatory for following the main flow of the chapters. Design is emphasized throughout the text. Switching algebra is developed as a tool for analyzing and implementing digital systems. The book contains an excellent presentation of minimization of combinational circuits, including multiple output ones, using the Karnaugh map and iterated consensus. There are a number of examples of the design of larger systems, both combinational and sequential, using medium scale integrated circuits and programmable logic devices. Introduction to Logic Design will provide students with the sort of grounding that will give them a solid foundation for further study, whether it be in a computer science, computer engineering, or electrical engineering program.